ANALISIS PENGARUH HARBOLNAS (Hari Belanja Online Nasional) PROGRAM SUBSIDI ONGKIR DAN PAY LETTER TERHADAP MINAT BELANJA KONSUMEN DI E-COMMERCE (Studi Kasus Kelurahan Lau Cih Medan Tuntungan) - Lestari Sihite; Helmina Simanjuntak (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
Harbolnas, postage subsidy program and pay letter are three facors that are of interest to fans of discounts in e-commerce. these three discounts are considered capable of increasing shopping interest in e-commerce amids the rise in onine purchases. This research show that harbolnas (X1) has not significat effect on shopping interest, the Subsidi Ongkir (X2) has a significant effect on shopping interest, and pay letter (X3) has a significant effect on shopping interest in e-commerce, case study Lau Cih Village, Medan Tuntungan District.